hiPSC-Derived Neurons Provide a Robust and Physiologically Relevant In Vitro Platform to Test Botulinum Neurotoxins - Lamotte, Juliette Duchesne De; Roqueviere, Sylvain; Gautier, Hélène; Raban, Elsa; Bouré, Céline; Fonfria, Elena; Krupp, Johannes; Nicoleau, Camille (Frontiers in Pharmacology, 2021)
Botulinum neurotoxins (BoNTs) are zinc metalloproteases that block neurotransmitter release at the neuromuscular junction (NMJ). Their high affinity for motor neurons combined with a high potency have made them extremely effective drugs for the treatment of a variety of neurological diseases as well as for aesthetic applications. Current in vitro assays used for testing and developing BoNT therapeutics include primary rodent cells and immortalized cell lines. Both models have limitations concerning accuracy and physiological relevance. In order to improve the translational value of preclinical data there is a clear need to use more accurate models such as human induced Pluripotent Stem Cells (hiPSC)-derived neuronal models. In this study we have assessed the potential of four different human iPSC-derived neuronal models including Motor Neurons for BoNT testing. We have characterized these models in detail and found that all models express all proteins needed for BoNT intoxication and showed that all four hiPSC-derived neuronal models are sensitive to both serotype A and E BoNT with Motor Neurons being the most sensitive. We showed that hiPSC-derived Motor Neurons expressed authentic markers after only 7 days of culture, are functional and able to form active synapses. When cultivated with myotubes, we demonstrated that they can innervate myotubes and induce contraction, generating an in vitro model of NMJ showing dose-responsive sensitivity BoNT intoxication. Together, these data demonstrate the promise of hiPSC-derived neurons, especially Motor Neurons, for pharmaceutical BoNT testing and development.